PERTUMBUHAN DAN HASIL KACANG HIJAU (Vigna radiata L. Wilczeck) YANG DIPUPUK N DENGAN DOSIS BERBEDA DAN PENYIANGAN - Rusmana, Rusmana (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2017)
The study was conducted to determine the effect of different doses of nitrogen fertilizer on the land without and with weeding. The experiments using factorial randomized block design were carried out at the Sitandu Curug Serang. The experimental results showed that the difference of dosage of N fertilizer up to 100 kg Urea ha-1 did not show the difference of green bean plant yield. Weeding once a week can increase the yield and the components of green beans about 78.3% both the number of pods per plant and the weight of seeds per plant. Keywords: green bean, nitrogen, weeding